PERANCANGAN BARU FASILITAS UMUM APARTEMEN DI JAKARTA PUSAT DENGAN PENDEKATAN BIOFILIK - Nabila Eka Putri, Jihan; Surya Rusyda, Hana faza; Zulfia Budiono, Irwana (Telkom University, 2024)
Jakarta, which is the capital city, certainly has many advantages and rapiddevelopment in various fields and is an opportunity to find work or become a target in business and others. To live in a metropolitan city, one of the things thatmust be faced isthe high life pressure and fast pace of life, which can be a sourceof stress and can have a negative impact on mental health. Vertical housing itself as a place of rest, but notonly that, the apartment is a long-term investment inthe mental health of its residents, because it includes the activities and lives of its residents. therefore the apartment isdesigned as a residential plan that accommodates the needs of metropolitan communities and creates supporting facilities Apartments that are good for mental health, reduceoccupant stress and prevent poor health due to the influence of the big city environment. Keywords: facilities apartments, interior, biophilic design.